Highlights of the Maritime Activities of the Algerian Fleet during Ottoman Rule - Chatra, Khireddine Youssef (Al-Adab Journal, 2020)
This paper explores the circumstances surrounding the emergence and development of the Algerian maritime struggle, often referred to as piracy, in the west of the Mediterranean in modern history. It also studies the conditions that lead to its emergence as the availability of vessels and defence structures. In discussing the existing the conditions during the founding of the Algerian navy during Ottoman rule and the nature of its activities from the religious, political and economic perspectives, the author reviews the political, economic, social, cultural and military roles of the country after its establishment and its effect on its relationship with the outer world. The paper also explores the mechanisms of organizing and equipping the fleet in order to highlight the contributions of the navy to the various sectors of the country and achieving an equilibrium in the nascent country’s international relations.